Markets and the state and the role of local regeneration strategies: a case study of the defence sector in the UK in the 1980s - Dabinet, Gordon; Dabinet, Gordon (European Spatial Research and Policy, 1994)
This paper reviews current practice and thinking in the UK with respect to changes occurring in the defence sector. Planned responses and interventionist measures to deal with the consequences of large scale job losses have not been adopted by the UK Government during the 1980s. However, many of the changes have been triggered or directly caused by the Government's own policies to create a free-trade and liberalised market economy. An opportunity has arisen for localities, through a growing loca! economic development function, to play a role in such readjustment. This paper examines the extent to which such !ocal responses can exercise any effective control over the future direction and impact of restructuring, and in particular address the role of the military-industrial complex, arms conversion and the Peace Dividend from this perspective.